2017
DOI: 10.1038/s41598-017-07746-z
|View full text |Cite
|
Sign up to set email alerts
|

Whole transcriptome profiling of taste bud cells

Abstract: Analysis of single-cell RNA-Seq data can provide insights into the specific functions of individual cell types that compose complex tissues. Here, we examined gene expression in two distinct subpopulations of mouse taste cells: Tas1r3-expressing type II cells and physiologically identified type III cells. Our RNA-Seq libraries met high quality control standards and accurately captured differential expression of marker genes for type II (e.g. the Tas1r genes, Plcb2, Trpm5) and type III (e.g. Pkd2l1, Ncam, Snap2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
73
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(87 citation statements)
references
References 89 publications
9
73
1
Order By: Relevance
“…; Sukumaran et al. ), gastrointestinal cells of mammals and teleost fish (Latorre et al. ; Mazzoni et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Sukumaran et al. ), gastrointestinal cells of mammals and teleost fish (Latorre et al. ; Mazzoni et al.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the lack of staining could be due to temporal, spatial, or developmental restrictions on expression. GNAT1 is also known to be expressed outside the eye in some vertebrates, including in the bitter taste receptors of mammals (He et al 2004;Sukumaran et al 2017), gastrointestinal cells of mammals and teleost fish Mazzoni et al 2013;Mazzoni et al 2015), and the pineal gland of zebrafish (Lagman et al 2015), and so might be present in these tissues in geckos as well. These alternative functions could account for the conserved selective constraint of the gene and its maintenance within gecko genomes.…”
Section: Discussionmentioning
confidence: 99%
“…While we previously reported that PLCβ3 is expressed in a subset of taste cells that are not Type II cells (Hacker et al, 2008), we have now demonstrated PLCβ3 is present in a subset of Type III cells. This idea is supported by recent RNA-sequencing analysis of individual Type II and Type III cells (Sukumaran et al, 2017) which identifies PLCβ3 expression in 30% of Type III cells. We searched this RNA-seq dataset of Type III cells (Sukumaran et al, 2017) to determine if other signaling components associated with PLCβ signaling are expressed in Type III taste cells.…”
Section: Discussionmentioning
confidence: 84%
“…This idea is supported by recent RNA-sequencing analysis of individual Type II and Type III cells (Sukumaran et al, 2017) which identifies PLCβ3 expression in 30% of Type III cells. We searched this RNA-seq dataset of Type III cells (Sukumaran et al, 2017) to determine if other signaling components associated with PLCβ signaling are expressed in Type III taste cells. We found that the alpha G-protein Gαq which activates PLCβ is expressed in these cells.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation